Anterior Cruciate Ligament Allograft Reconstruction Outcome Independent of Patient’s Age - Parimal Rana; Jane Brennan; Anagh Astavans; Sneha Kuppireddy; Christina Morganti; Benjamin M Petre; Andrea Johnson; Justin J Turcotte; Daniel Redziniak (Journal of Orthopedics, Traumatology and Rehabilitation)
Introduction: Anterior cruciate ligament reconstruction (ACLR) is a widely performed surgical procedure to restore knee stability following an ACL tear. While previous studies have explored the impact of age on ACLR outcomes, the specific influence of age on allograft ACLR remains relatively debatable. This study aims to investigate the relationship between age and allograft failure rates in ACLR. Materials and Methods: This retrospective study included 482 patients who underwent primary ACLR using a bone patella tendon bone allograft. Data on patient demographics, comorbidities, and postoperative outcomes were collected. Univariate analysis was conducted to identify any significant differences between the age groups. All statistical analyses were performed using R Studio. Results: Among the observed age groups, older individuals had a higher prevalence of comorbidities, including anxiety or depression (P = 0.043), hypertension (P < 0.001), and sleep apnea (P = 0.029). There were no significant differences in postoperative outcomes, including 90-day emergency department visits, 90-day postoperative admissions, or ACL retear with or without revision surgery at an average follow-up of 2 years, among the different age groups. The same was found when examining differences between patients <50 and patients 50 or older. Discussion and Conclusions: The results of the current study demonstrate that age does not significantly impact allograft ACLR outcomes. Age alone should not be the sole determining factor when considering ACL surgery, emphasizing the importance of personalized factors in decision-making.